Early Resolved Acute Syphilitic Posterior Placoid Chorioretinitis. Issue 4 (April 2015) - Ji, Yong-Sok; Yang, Jee Myung; Park, Sang-Woo
ABSTRACT: Purpose: Acute syphilitic posterior placoid chorioretinitis (ASPPC) is a rare ocular manifestation of syphilis, and its natural course is not well understood. We herein present two unusual cases of ASPPC in which there was almost total resolution of the fundus and optical coherence tomography (OCT) findings during the early presentation before treatment was initiated. Case Reports: Patient 1: A 44-year-old man presented with a 4-day history of decreased visual acuity in his left eye. Dilated fundus examination revealed a yellowish subretinal placoid lesion in the posterior pole, and OCT images showed subretinal fluid and irregular or granular hyperreflectivity of the retinal pigment epithelium. Ten days later, the yellowish placoid lesion had dramatically improved and the OCT findings showed absence of the subretinal fluid and hyperreflective lesion without any treatment. Patient 2: A 35-year-old man presented with a 3-day history of decreased visual acuity in his right eye. Dilated fundus examination showed a yellow submacular placoid lesion, and OCT images showed a small amount of subretinal fluid with disruption of the inner segment/outer segment junction. Four days after presentation, the fundus and OCT findings had markedly resolved without definitive treatment. In both cases, serologic test results confirmed the diagnosis of syphilis, and the patients were referred to the Department of Infectious Disease for systemic antibiotic treatment. After treatment, the patients' visual acuities were improved, but the disruption of the inner segment/outer segment junction on OCT images remained. Conclusions: In patients with ASPPC, fundus and OCT findings can spontaneously recover during the early clinical course before treatment.